The Course of Actualization - De Smet, Hendrik (Language (Baltimore), 2012)
Actualization is traditionally seen as the process following syntactic reanalysis whereby an item's new syntactic status manifests itself in new syntactic behavior. The process is gradual in that some new uses of the reanalyzed item appear earlier or more readily than others. This article accounts for the order in which new uses appear during actualization. Five corpus-based case studies are presented involving reanalysis and actualization in different functional domains of grammar. These include the reanalysis of "all but, far from", and Dutch "verre van" to adverbial downtoners, and the reanalysis of "fun" and "key" from nouns to adjectives. It is shown that actualization proceeds from one environment to another on the basis of similarity relations between environments. The similarity relations may involve broad syntactic generalizations but also superficial similarities to existing patterns, including even an item's uses prior to reanalysis. Because actualization is guided by local and global analogies to existing uses, one determinant of the course of actualization is the locus of reanalysis, as it defines the first uses of an item under change, on which subsequent uses can be modeled. It also follows that the course of actualization is both item-specific and language-specific. The findings presented challenge the concept of reanalysis, which appears less abrupt than usually assumed. Further, it is argued that the findings fit best with usage-based models of language, which attribute a prominent role to similarity-based organization in grammar, and in which an item's use can be subject to multiple, potentially conflicting generalizations.